Virulence markers, adhesion and biofilm formation of Escherichia coli strains isolated from drinking water supplies of north Paraná State, Brazil. (16th August 2022) - Schüroff, Paulo Alfonso; Andrade, Fernanda Batista; Pelayo, Jacinta Sanchez
Abstract: Waterborne diseases are a major public health problem responsible for a high number of deaths worldwide, of which Escherichia coli is a major agent of contamination. This study investigates the occurrence of different diarrheagenic E. coli (DEC) pathotypes and its relationship with adherence patterns and biofilm formation. Between 2012 and 2014, a total of 1, 780 drinking water samples were collected from different rural communities and urban water systems of north Paraná State. A total of 14% were positive for E. coli and 250 non-duplicate E. coli isolates were obtained. Between the E. coli isolates, 28 (11.2%) harbored DEC-associated genes, 10.7% being classified as Shiga toxin-producing E. coli (STEC), 64.3% enteroaggregative E. coli (EAEC) and 25% atypical enteropathogenic E. coli (aEPEC). The aggregative adherence (AA) was the predominant adherence pattern (84%), significantly associated with biofilm formation ( p < 0.0001). On the other hand, the AA pattern and biofilm formation were not significantly associated to DEC pathotypes ( p > 0.05). Therefore, we proposed that the AA pattern and biofilm formation in E. coli isolated from drinking water supplies could be associated with adherence and colonization of abiotic surfaces, such as pipes, leading to persistence and resistance to treatment or disinfection. HIGHLIGHTS: This study shows the relationship between DEC and non-DEC strains and adherence/biofilm formation. The AA-positive strains were predominant and significantly associated to biofilm formation. DEC and non-DEC strains present similar adherence patterns and biofilm formation values. The AA pattern and biofilm formation could be responsible for the ability of these strains to persistence and resistance in the environment. Graphical Abstract